Assessment Model Implemented in Learning Gallery to Teach Cross Cultural Understanding for EFL Learners - Iftanti, Erna (Dinamika Ilmu, 2018)
In response to one of the demands for EFL learners to have cross cultural competence mainly on cultures of English speaking countries, this article describes assessment model implemented in Learning Gallery technique to teach Cross Cultural Understanding. Learning Gallery as one of the innovative ways of teaching content courses with an abundant coverage of materials proves to be able to help learners to be competent in some topics of cultures. This fact has been proved by implementing assessment model, namely Student-Self Test and Teacher-Made Test. The result of this study reveals that such an assessment model brings about improving the students’ cross cultural competence and leads them to be more independent learners. Moreover, through a reflective interview given at the end of the course, they claim that by developing their own test and doing their peer’s made test, they are experienced in test development in addition to be better prepared for the test. Accordingly, this study gives a meaningful insight for EFL lecturers teaching content courses to implement Learning Gallery technique with such an assessment model in order to help the EFL learners to be autonomously independent learners and competent in their own subjects learnt.